Prevalence and risk factors of gestational diabetes mellitus in Nanning, Guangxi, China: a cross-sectional study - Chen, Binlin; Jiang, Rui; Pan, Xiuhua; Huang, Jing (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to investigate the prevalence of gestational diabetes mellitus (GDM), its associated risk factors, and perinatal outcomes among pregnant women in Nanning, the capital city of Guangxi, China.MethodsA retrospective analysis of a cross-sectional dataset was conducted using data from 2003 pregnant women who underwent prenatal care and completed a 75g oral glucose tolerance test (OGTT) at 24–28 weeks of gestation during the year 2021 at the Maternity and Child Health Care of Guangxi Zhuang Autonomous Region in Nanning. Demographic, anthropometric, and clinical data were collected. Statistical analyses included univariate analysis, multivariable logistic regression (adjusted for pre-pregnancy BMI, parity, educational level, and family history of diabetes), and restricted cubic spline (RCS) models to explore dose-response relationships.ResultsA total of 375 cases of GDM were identified, yielding a prevalence of 18.72% (95% CI: 17.10%–20.34%). Women with GDM were significantly older (mean age: 31.62 vs. 30.62 years, P < 0.001) and shorter (mean height: 158.1 cm vs. 159.0 cm, P < 0.001) compared to non-GDM women. Multivariable logistic regression showed that age ≥ 30 years (OR = 1.61, 95% CI 1.25–2.08, P < 0.001) and height < 159.0 cm (OR = 1.27, 95% CI 1.01–1.61, P = 0.048) were independent risk factors for GDM. Restricted cubic spline models confirmed a positive dose-response between age and GDM risk, and a linear inverse relationship between height and GDM risk (both P for overall < 0.05). Additionally, the GDM group exhibited a higher incidence of preterm birth (8.76% vs. 4.92%, P = 0.030).ConclusionsThe prevalence of GDM in Nanning, Guangxi, southern China is high. Older maternal age (≥30 years) and shorter stature (<159.0 cm) are independently associated with increased GDM risk in this urban population. These findings highlight the need for targeted screening and preventive strategies for high-risk groups in Nanning.